Complications of Total Colectomy with Ileorectal Anastomosis: Case Study of Terminal Ileum Perforation - Julia Pelayo Rodríguez; Andoni Alaba Sorabilla; Oihan Loidi Lázaro-Carrasco; Rubén Gonzalo González; Ruben Caiña Ruiz; Berta Martín Rivas; José Manuel Gutiérrez Cabezas (Medicine and Medical Research: New Perspectives Vol. 11, 2024)
Total colectomy followed by ileorectal anastomosis is an established operation that may be employed as a surgical solution for a variety of colonic diseases. Postoperative morbidity and mortality rates are generally considered low, with most patients rating the functional outcomes as good to excellent. The ileorectal anastomosis is usually latero-terminal and is constructed with staples. If the segment of the terminal ileum extending beyond the anastomosis site is too long, it may remain as an appendage, which can fold or twist upon itself, causing intermittent closed-loop obstruction at its tip. This can lead to localized perforation, sepsis, and eventually the formation of a fistula. In conclusion, total colectomy with ileorectal anastomosis is a safe procedure with good functional outcomes, though there is a high risk of postoperative intestinal obstruction, and distal ileum perforation is a rare but possible complication. A case is reported of a patient who developed significant complications from this portion of the bowel.